2017
DOI: 10.1080/15384047.2017.1345383
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of eIF2β lysine stretches creates a dominant negative that affects the translation and proliferation in human cell line: A tool for arresting the cell growth

Abstract: eIF2β is involved in the protein synthesis process and should act in nuclear processes as well. eIF2βΔ3K reduces cell proliferation and causes cell death. Since translation control is essential for normal cell function and survival, the development of drugs or molecules that inhibit translation has become of great interest in the scenario of proliferative disorders. In conclusion, our results suggest the dominant negative eIF2βΔ3K as a therapeutic strategy for the treatment of proliferative disorders and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Consistent with our hypothesis, an array of studies have demonstrated that eIF4A3 can promote the back-splicing reaction by directly interacting with the flanking sequence of circularizing exons in mammalian cells ( 92–94 ). Since several eIFs have been reported as nucleocytoplasmic shuttling proteins ( 95–97 ), the nuclear functions of eIFs should be taken into consideration in future.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our hypothesis, an array of studies have demonstrated that eIF4A3 can promote the back-splicing reaction by directly interacting with the flanking sequence of circularizing exons in mammalian cells ( 92–94 ). Since several eIFs have been reported as nucleocytoplasmic shuttling proteins ( 95–97 ), the nuclear functions of eIFs should be taken into consideration in future.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that eIF2β mediates autophagy defects via mechanisms independent of ISR, since eIF2β has functions independent of eIF2 39,40 . For example, suppression of eIF2β has been reported to slow down cancer cell growth 39 . In developing neurons, eIF2β can directly interact with the translational repressor Kra to regulate midline axon guidance 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro experiments, the knockdown of eIF2β manipulations induced G1 cell cycle arrest in both NCI-H358 and NCI-H460 cells [ 23 ]. Deleting the polylysine stretches in the amino-terminal region of eIF2β decreased protein synthesis, inhibited cell proliferation and viability, increased cell death, and induced G2 cell cycle arrest in Hek293TetR cells [ 24 ]. Interestingly, we noticed that the levels of EIF2β in somatotroph adenomas were related to the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%